PROFIL PEMAHAMAN KONSEP MATEMATIS DALAM MENYELESAIKAN MASALAH OPERASI HITUNG BILANGAN BULAT SISWA KELAS VII SMPK BALA KESELAMATAN PALU - Yesinta Natasya; Fajriani Fajriani; Ibnu Hadjar; Baharuddin Paloloang (Universitas Tadulako, 2025)
Research This research aims to obtain a description of the profile of students' mathematical concept understanding mathematical concept understanding profile of students in solving integer counting operations. The type of This research is a qualitative research. The subjects in this study were three students of class VII B SMPK Bala Keselamatan Palu consisting of one student with high mathematical ability, one student with high mathematical ability, and one student with high mathematical ability. student with high mathematical ability, one student with medium mathematical ability, and one student with low mathematical ability. mathematical ability, and one student with low mathematical ability. Data on students' concept understanding were obtained by written assignments and interviews. The results of this study refer that (1) Profile of students' mathematical concept understanding with the subject of high mathematical ability that the subject can identify and state all Polya indicators used in the research well, starting from understanding the problem, planning the problem, and solving the problem. well, starting from understanding the problem, planning the solution, to verifying the results. results. Also can use other solution methods and understand all the data given. data given. (2) The profile of students' mathematical concept understanding with the subject of moderate mathematical ability, namely the subject can identify most of the Polya indicators used in the study well, although there are doubts in determining the right solution method and difficulties in understanding all the data given. doubts in determining the right solution method and difficulty in solving the problem in different ways. solving the problem in a different way. Also can use data well, but well, but not fast enough to understand the problem as a whole. (3) Profile of understanding mathematical concept understanding profile of students with low mathematical ability subjects, namely the subject is able to understand some indicators well. able to understand some indicators well. Subjects often hesitate in determining determining the solution method and could not check the correctness of the results obtained. obtained. Also unable to identify all Polya indicators well, especially in understanding the problem and checking the argument given.